Ambient assisted living : Italian forum 2016 - Cavallo, Filippo; Marletta, Vincenzo; Monteriù, Andrea; Siciliano, P. (Springer, 2017)
This book documents the state of the art in the field of ambient assisted living (AAL), highlighting the impressive potential of novel methodologies and technologies to enhance well-being and promote active ageing. The coverage is wide ranging, with sections on assistive devices, elderly people monitoring, home rehabilitation, ICT solutions for AAL, living with chronic conditions, robotic assistance for the elderly, sensing technologies for AAL, and smart housing. The book comprises a selection of the best papers presented at the 7th Italian Forum on Ambient Assisted Living (ForitAAL 2016), which was held in Pisa, Italy, in June 2016 and brought together end users, technology teams, and policy makers to develop a consensus on how to improve provision for elderly and impaired people. Readers will find that the expert contributions offer clear insights into the ways in which the most recent exciti ng advances may be expected to assist in addressing the needs of the elderly and those with chronic conditions.
Keywords: Assistive computer technology -- Congresses.; Ambient intelligence -- Congresses.; Self-help devices for older people -- Congresses.; Home automation -- Congresses.; Biomedical engineering -- Congresses.; elektronické knihy; electronic books